Systemic Regulatory Abnormalities in Glycemic Control and its Relation with Depression - A Cross-Sectional Study - M, Aravindh; Kailash, Shabeeba Z; Sureshkumar, Kailash (International Journal of Experimental Research and Review, 2024)
Globally, depression is the 3rd leading cause of disability-adjusted life years. The presence of depression and its symptoms has been associated with improper control of glucose and poor glycemic index and a bidirectional relationship was seen between depressive disorders and diabetes mellitus. Depression, even at subclinical levels, has the tendency to increase the risk of incident type 2 diabetes by 25–60%. This study aims to find the prevalence of Type 2 diabetes mellitus(T2DM) in depression patients and to find the relationship between the severity of depression and the severity of T2DM in a Cross-sectional study. A total of 178 patients who attended psychiatry OPD of a tertiary healthcare hospital for a study period of 6 months were recruited into the study after considering inclusion and exclusion criteria evaluated by an experienced psychiatrist. Details like sociodemographic profiles and clinical data related to Major depression and T2DM were collected through self-structured proforma. To assess the severity of depression, HAM-D scale was used and the glycemic severity measure was used to assess the severity of T2DM by a well-trained psychiatrist. Statistical analysis was done and results were framed. The prevalence of Type 2 Diabetes mellitus in depressive disorder patients was found to be 25.2%. A significant association was seen between the severity of T2DM and the severity of depression, with a p-value of 0.013 and a chi-square value of 12.699. Significance with certain clinical factors like insulin usage (F=5.635; p = 0.019) and drug compliance (F=16.841; p <0.001) was seen in T2DM patients with depression. Nearly ¼th of the patients with depression had T2DM and the severity of hyperglycaemia was also found to be high as those patients were on insulin administration, other medical comorbidity disorders were present and drug compliance was found to be poor. Triglyceride glucose index was also found to be high in patients with severe depression, which contributes to improper blood glucose balance. Treating and reducing both the severity of T2DM and depression simultaneously is needed to improve the functioning of the patients and improve the retention in treatment and drug compliance, thereby preventing morbidity and mortality.